Polypyrrole-based sensors for volatile organic compounds (VOCs) sensing and capturing: A comprehensive review - Miah, Mohammad Raza; Yang, Minghui; Khandaker, Shahjalal; Bashar, M Mahbubul; Alsukaibi, Abdulmohsen Khalaf Dhahi; Hassan, Hassan M.A.; Znad, Hussein; Awual, Md. Rabiul (Sensors and actuators. A. Physical., 2022)
Smart and precise sensing is very important for the protection of both environment and personal security in modern civilized society. There are numerous sensing devices for detecting physical and chemical changes such as temperature, humidity, pressure, and chemical species. In this regard, conducting polymers is at the core of attention for the fabrication of next-generation sensor applications. Polypyrrole (PPy), is one of the emerging intelligent materials with a wide range of applications in the field of optical, electronic, and electrochromic devices and sensors. The stability in a different environment, ease of deposition from aqueous and non-aqueous media, adherence to diverse substrates, and high electrical conductivity made PPy a unique choice for sensor development. In recent years, PPy has proven an excellent candidate for sensing volatile organic compounds (VOCs) due to its selectivity and sensitivity towards target gas molecules, and detection of inorganic gases and VOCs. Consequently, to develop outstanding sensing devices attempts have been dedicated to developing PPy-based sensors for excellent mechanical and electrochemical performance. This review aims to provide a recent overview of progress in PPy-based advanced sensing devices. This review aims to provide a recent overview of progress in PPy-based advanced sensing devices. We have systematically discussed the challenges and future development of various sensing devices. Furthermore, the current understanding and performance evaluation of gas sensing mechanisms in PPy-based sensors are discussed theoretically and experimentally. We have also identified gaps in the state-of-the-art and hope that this study would lead to further research works into using PPy to make gas sensors. Finally, the future directions of various sensors with advanced PPy-based sensing systems have been prospected. [Display omitted] •Polypyrrole (PPy) was an excellent candidate for capturing a broad range of VOCs.•Doping, surface modification, side-chain selection, and PPy-chain-arrangements were reported.•The complementary roles of experimental and theoretical studies were clearly described.•Reported families of PPy and their current utilities were elaborated.•Gaps were identified both from fundamental and applied standpoints.